PROBLEMATIKA DALAM IMPLEMENTASI LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH - Yulianti Yulianti; Nurwahidah Marliana; Zahara Al Munawaroh; Zidan Alhamdika (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Education to carry out guidance and counseling in schools is an element related to services in schools. The coordinator or implementer is the supervising teacher and the person who gives advice. Consultation is a method of support provided to parties consulted during meetings so that the consultation process has the ability to see and find problem points and solutions to problems. In the process of advising or supporting counselees, counselees systematically express their problems, have the ability to accept themselves according to their potential, and help solve problems with their potential. In implementing counseling guidance services, many students do not clearly understand the duties, functions and role of counseling guidance. Elements that are proven to be in accordance with existing practices in the field of guidance and counseling can be used as a forum for advising and motivating problems in order to find solutions that suit one's abilities. An interview or debrief is a tool for gathering information by revealing several problems and receiving a good response.Keywords: Problems, Implementation, Guidance and Counseling